FORMULASI PAKAN UNGGUL BERBASIS BIOTEKNOLOGI LIMBAH ORGANIK LOKAL UNTUK IKAN LELE ORGANIK KUALITAS EKSPOR - Yusafir Hala; syahruddin udin kasim; Indah Raya (KOVALEN: Jurnal Riset Kimia, 2019)
Research on Superior Feed Formulations Based on Local Organic waste Biotechnology for Export quality organic Catfish. Research Objective: The discovery of feed types of tilapia and organic catfish that have export quality nutritional content based on the best quality local marine organic waste through a touch of biotechnology. Furthermore, the complete chemical composition of the waste used and feed components is obtained. Research Methods: Determine the best composition of biomass of marine organic waste and local onshore organic wastes with the highest levels of protein and carbohydrates and integrated with other wastes. The nutritional content is analyzed, namely: Carbohydrates, fats, proteins, and supporting minerals, namely: Fe, K and Ca. Instrumentation used to support the research objectives is AAS and HPLC. Research Results: Export quality organic catfish pellet feed in the form of waste: marine fish, sea shrimp waste, sea crab waste, rice bran waste, corn waste, mixed organic waste, golden snail waste, seaweed waste and coconut water waste respectively (27; 15; 7.5; 33; 3; 2.5; 5; 2.5 and 2) %b/ b, starch 2% b/b and marine phytoplankton biomass 0.5% b/b. The nutritional content of organic catfish pellets that have been produced, namely: 51% protein b/b, 24% carbohydrate b/b, 9% fat b/b, crude fiber 8%b/b, water content 2 - 2.5%b/b, mineral Fe 1% b/b, mineral K 1% b/b, mineral Ca 1%b/b, ash content 2 - 2.5%b/b. Feed packing for export quality organic catfish pellets is given the "SANTARI-KU" label. Keywords: Superior feed, local organic waste biotechnology, export quality organic catfish, Santari-ku.